Lipid Transport in Brown Adipocyte Thermogenesis - Wade, Gina; McGahee, Ayren; Ntambi, James M.; Simcox, Judith (Frontiers in Physiology, 2021)
Nonshivering thermogenesis is an energy demanding process that primarily occurs in brown and beige adipose tissue. Beyond regulating body temperature, these thermogenic adipocytes regulate systemic glucose and lipid homeostasis. Historically, research on thermogenic adipocytes has focused on glycolytic metabolism due to the discovery of active brown adipose tissue in adult humans through glucose uptake imaging. The importance of lipids in nonshivering thermogenesis has more recently been appreciated. Uptake of circulating lipids into thermogenic adipocytes is necessary for body temperature regulation and whole-body lipid homeostasis. A wide array of circulating lipids contribute to thermogenic potential including free fatty acids, triglycerides, and acylcarnitines. This review will summarize the mechanisms and regulation of lipid uptake into brown adipose tissue including protein-mediated uptake, lipoprotein lipase activity, endocytosis, vesicle packaging, and lipid chaperones. We will also address existing gaps in knowledge for cold induced lipid uptake into thermogenic adipose tissue.